2017
DOI: 10.1016/j.ibiod.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Zinc toxicity stimulates microbial production of extracellular polymers in a copiotrophic acid soil

Abstract: The production of extracellular polymeric substances (EPS) is crucial for biofilm structure, microbial nutrition and proximal stability of habitat in a variety of environments. However, the production patterns of microbial EPS in soils as affected by heavy metal contamination remain uncertain. Here we investigate the extracellular response of the native microbial biomass in a grassland soil treated with refined glycerol or crude unrefined biodiesel co-product (BCP) with and without ZnCl2. We extracted microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…For example, Pal and Paul (2013) reported a decrease in EPS production with an increase in nickel concentration. On the other hand, Redmile-Gordon and Chen (2017) found that zinc may stimulate EPS production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pal and Paul (2013) reported a decrease in EPS production with an increase in nickel concentration. On the other hand, Redmile-Gordon and Chen (2017) found that zinc may stimulate EPS production.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc contaminated soil has negative impacts on plants as well as soil microbiome however, such soils are enriched with Zn tolerant PGPR hence, the soil sampling is one of the critical criteria for the isolation of such Zn tolerant PGPRs 17 . Many areas in Rajasthan including the Zawar region are contaminated with the toxic amounts of Zn and other heavy metals due to ore mining and other human activities 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Zn in accelerating carbonate formation is also identified in marine organisms, where CA, a Zn-containing enzyme, regulates biogenic carbonate formation, as documented in corals 49 , sponges 28 , and other metazoans 50 . The catalytic mechanism of CA involves the attack of Zn-bound OH − on a CO 2 molecule loosely bound in the active center of the enzyme, and the resulting Zn-coordinated HCO 3 − ion is then displaced from the metal ion by H 2 O. Zinc also stimulates the production of extracellular polymeric substances 51 , which have been shown to catalyse dolomitization 20 . Zinc is an essential trace nutrient for marine microorganisms, as demonstrated by the typical nutrient cycling profile of Zn concentrations in the ocean, with surface depletion due to phytoplankton uptake and regeneration at depth by remineralization of sinking organic matter.…”
Section: Discussionmentioning
confidence: 99%